Chaosgraphies city - Araujo, Frederico (Pontifícia Universidade Católica de São Paulo, 2016)
Chaosgraphies refers to a means of collective construction of discourses that navigates among science, art and philosophy. It uses cartographic practice as affective plotting, associated with the notion of chaos as a possibility of “becoming”. It can be understood as a “chaotic” means of graphical composition towards the creation of discourses, or as a corporeal/word-based adventure that seeks to establish tensions in the process of instituting and narrating experiences of objects. Chaosgraphies, therefore, are “deconstructed happenings:” rather than being “scorched earth” practices, they signal an intention in which experience problematizes logocentric speech by overturning absolutes and also through poietic transgression. Chaosgraphies city exercises this chaosgraphical means of constructing discourses whose theme is “the city.”